2003
DOI: 10.1080/0003684022000018259
|View full text |Cite
|
Sign up to set email alerts
|

The demand for casino gaming

Abstract: In this study an econometric model is developed to examine the determinants of the demand for casino gaming, specifically the demand for slot machine wagering at riverboats and racinos. In addition to examining the effects of traditional demand variables, the effect on wagering of variables such as location of a wagering facility and of government restrictions, is examined. A unique measure of accessibility of market area customers to a facility and to competing facilities was developed. The demand for wagerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(40 citation statements)
references
References 17 publications
2
38
0
Order By: Relevance
“…The only lack of significance at the 5 percent level was for Statejur when only populations greater than 1,000 were used, but the estimated odds ratio was still 8.2. (4) I estimated the model with quadratic specifications for each of the income variables to be consistent with Thalheimer and Ali (2003). Doing so had a negligible effect on the coefficient estimates of Multstate and Statejur.…”
Section: Estimation Of Casino Size and Timingmentioning
confidence: 99%
See 1 more Smart Citation
“…The only lack of significance at the 5 percent level was for Statejur when only populations greater than 1,000 were used, but the estimated odds ratio was still 8.2. (4) I estimated the model with quadratic specifications for each of the income variables to be consistent with Thalheimer and Ali (2003). Doing so had a negligible effect on the coefficient estimates of Multstate and Statejur.…”
Section: Estimation Of Casino Size and Timingmentioning
confidence: 99%
“…Income is an important determinant of casino demand (Thalheimer and Ali 2003 per capita income for Indian reservations, adjacent counties, the nearest metropolitan area of 1 million people, and the reservation's state; all income variables are measured in 1989 dollars. Despite the need to control for the effects of income, no prediction can be made regarding the direction of the income coefficients in the Casino regressions.…”
Section: Appendix B Ex Ante Predictions For Control Variablesmentioning
confidence: 99%
“…Studies have been conclusive and evidence suggests that the presence of pari-mutuel racing, live or simulcast, increases EGM gambling (Thalheimer, 1998(Thalheimer, , 2008(Thalheimer, , 2012. One study (Thalheimer & Ali, 2003) found a negative impact on EGM revenue, but the relationship was statistically insignificant. We can therefore conclude that the impact of pari-mutuel or race betting on EGM gambling is complementary.…”
Section: Pari-mutuel or Race Bettingmentioning
confidence: 99%
“…Seven of these 10 studies found that casinos substitute for other casinos, measured notably as decreases in gross gambling revenue (GGR), patronage, and admissions (Eadington, Wells, & Gossi, 2010;Gallagher, 2014;McGowan, 2009;Nichols, 1998;Shonkwiler, 1993;Thalheimer & Ali, 2003;Walker & Jackson, 2008;Walker & Nesbit, 2014). Three studies found either a complementary relationship or no impact (Geisler & Nichols, 2016;Hunsaker, 2001;Walker & Jackson, 2008).…”
Section: Casinosmentioning
confidence: 99%
See 1 more Smart Citation